KONFIGURASI PEMIKIRAN AL-QABISI TENTANG PENDIDIKAN ISLAM - Muslim Musir (POTENSIA: Jurnal Kependidikan Islam, 2016)
As a jurist, Hafiz al-Qur`an and hadith as well as a good understanding Arabic, al-Qabisi offer educational concepts based al-Qur`an and Sunnah, which impressed normative paradigm of thinking. However, the environmental conditions when it still has relevance to the concept offers, so that form the guidelines for teaching children during the fourth century hijrah. In principle, the development of the Islamic education concept does not just stop in textual normative, need depth assessment of various aspects, sociological, geographical, or philosophy of a nation itself. Very unlikely set curriculum or teaching methods and educational purposes based on one aspect only. Advanced education in the perspective of al-Qabisi can be seen from the realization of the religious environment in the various regions of Islam at the time. Is a natural thing when he established the concept of education that guided in his time.